1985
DOI: 10.1111/j.1399-3054.1985.tb03346.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethephon and auxin induce mycorrhiza‐like changes in the morphology of root organ cultures of Mugo pine

Abstract: The effects of ethylene and auxin on the morphology and anatomy of root organ cultures of Pinus mugo Turra var. mugo were investigated to test the hypothesis that changes in root morphology associated with formation of ectomycorrhizae may be related to ethylene produced by ectomycorrhizal fungi or by host plant roots in response to fungus‐produced auxin. Morphological changes characteristic of mycorrhizal infection include dichotomous branching of lateral roots, inhibition of root hair formation and enlargemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 15 publications
6
29
0
Order By: Relevance
“…Treatment with 2-chloroethylphosphonic acid (CEPA or ethephon) induced dichotomous and coralloid branching on roots of Pinus radiata seedlings (Wilson & Field, 1984). Treatment of cultured P. mugo roots with CEPA also induced mycorrhiza-like changes including dichotomous branching and the formation of coralloid structures (Rupp & Mudge, 1985 ;Rupp et al, 1989), although the effects of CEPA and of silver thiosulphate, an inhibitor of ethylene action, on P. mugo seedlings were difficult to interpret (Rupp et al, 1989) ; the authors of those studies concluded that auxin might also act both through ethylene and through ethylene-independent mechanisms. The ability of ethylene to reduce auxin transport (Suttle, 1988), and the stimulation of ethylene biosynthesis by auxin, raise questions regarding the interpretation of the previously observed effects of auxin and ethylene on dichotomous branching in cultured roots.…”
Section: mentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment with 2-chloroethylphosphonic acid (CEPA or ethephon) induced dichotomous and coralloid branching on roots of Pinus radiata seedlings (Wilson & Field, 1984). Treatment of cultured P. mugo roots with CEPA also induced mycorrhiza-like changes including dichotomous branching and the formation of coralloid structures (Rupp & Mudge, 1985 ;Rupp et al, 1989), although the effects of CEPA and of silver thiosulphate, an inhibitor of ethylene action, on P. mugo seedlings were difficult to interpret (Rupp et al, 1989) ; the authors of those studies concluded that auxin might also act both through ethylene and through ethylene-independent mechanisms. The ability of ethylene to reduce auxin transport (Suttle, 1988), and the stimulation of ethylene biosynthesis by auxin, raise questions regarding the interpretation of the previously observed effects of auxin and ethylene on dichotomous branching in cultured roots.…”
Section: mentioning
confidence: 99%
“…( O #% , 0n2 µM thiamine HCl, 0n6 µM pyridoxine HCl and 222 mM glucose (Rupp & Mudge, 1985). The medium containing all ingredients with the exception of thiamine and pyridoxine was sterilized by autoclaving.…”
Section: Establishment Of Pine Root Organ Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…These morphological modifications were suppressed if the hormonal treatment was interrupted. Similarly, Rupp & Mudge (1985) showed that ethylene and auxin induce mycorrhizalike roots on Pinus mugo. Gruhn, Gruhn & Miller (1992) obtained mycorrhiza-like roots on Pinus densiflora inoculated with Boletinellus merulioides although no mycorrhiza was formed ; they correlated these effects with production of IAA in the culture medium by the ectomycorrhizal fungus.…”
mentioning
confidence: 99%
“…8,[10][11][12][13][14][15] The formation of dichotomous roots has been suggested to result from changes in either auxin or ethylene concentrations due to the fungal growth in the root. [15][16][17][18] …”
Section: Introductionmentioning
confidence: 99%